Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2020 Division Public Relations Coordinator - Siti Hawa .; Agus Naryoso M.Si; Much Yulianto M.Si; Joyo M S Gono; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This field is motivated by the work of Mayor and Deputy Mayor Candidate Solok No. 3 which requires a political campaign to win Irzal Public Relations Ilyas and Alfauzi Bote as Mayor and Deputy Mayor of Solok period 2016-2020. In this case, the division of Public Relations Coordinator perform activities with the objective to design a two-way communication that is engaged in activities through events, third party endorsers, community relations, and Social media. The event was held for 2 months and successfully relation to religious and traditional leaders in the 8 villages of 13 urban villages, 10 communities and 13 urban villages ‘blusukan’. In addition, field work shows that “Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2020” was successful.